Alcohol fuels - Полункін, Є.В.; Зубенко, С.О.; Гайдай, О.О.; Кузнєцова, О.В. (Proceedings of National Aviation University, 2010)
The existing motor fuel alternative, namely alcohol - biomethanol, bioethanol and biobutanol, the possibility of using them in different concentrations of gasoline were consider. From the most perspective of considered alternative fuels for were shows.